The girl from the papers [large type] - Wright, Jennifer L. (Thorndike Press large print Christian fiction, 2023)
"Beatrice Carraway has dreams. Although she's aged out of the childhood pageant circuit, she's intent on carrying her talents all the way to the big screen--if only she can escape the poverty of West Dallas first. But as the Great Depression drags the working class further and further under, Beatrice struggles just to keep herself, her mother, and her younger sister afloat. After a string of failed auditions, she feels defeated.And then in walks Jack Turner. Though Beatrice is determined to pull herself up by her bootstraps, Jack has decided on a different path out of the gutters. It isn't long before Beatrice is swept into an exciting and glamorous life of crime beside the man she loves. Keeping one step ahead of the law, she sees her dreams of fame come true when her name and picture are plastered in newspapers across the country. Yet as their infamy grows, the distance between them widens. While Jack begins seeking bigger payouts and publicity, Beatrice starts to long for a safe, quiet life and something deeper to fill the emptiness in her soul. But when the danger of Jack's schemes ratchets up, Beatrice fears her dreams--and her future--will end up going down in a hail of bullets" --